Bv8 Blockade Sensitizes Anti-PD1 Therapy Resistant Tumors - Benguigui, Madeleine; Vorontsova, Avital; Timaner, Michael; Levin, Sapir; Haj-Shomaly, Jozafina; Deo, Abhilash; Menachem, Rotem; Manobla, Bar; Cooper, Tim J.; Raviv, Ziv; Shaked, Yuval (Frontiers in Immunology, 2022)
Myeloid-derived suppressor cells (MDSCs) are known to promote tumor growth in part by their immunosuppressive activities and their angiogenesis support. It has been shown that Bv8 blockade inhibits the recruitment of MDSCs to tumors, thereby delaying tumor relapse associated with resistance to antiangiogenic therapy. However, the impact of Bv8 blockade on tumors resistant to the new immunotherapy drugs based on the blockade of immune checkpoints has not been investigated. Here, we demonstrate that granulocytic-MDSCs (G-MDSCs) are enriched in anti-PD1 resistant tumors. Importantly, resistance to anti-PD1 monotherapy is reversed upon switching to a combined regimen comprised of anti-Bv8 and anti-PD1 antibodies. This effect is associated with a decreased level of G-MDSCs and enrichment of active cytotoxic T cells in tumors. The blockade of anti-Bv8 has shown efficacy also in hyperprogressive phenotype of anti-PD1-treated tumors. In vitro, anti-Bv8 antibodies directly inhibit MDSC-mediated immunosuppression, as evidenced by enhanced tumor cell killing activity of cytotoxic T cells. Lastly, we show that anti-Bv8-treated MDSCs secrete proteins associated with effector immune cell function and T cell activity. Overall, we demonstrate that Bv8 blockade inhibits the immunosuppressive function of MDSCs, thereby enhancing anti-tumor activity of cytotoxic T cells and sensitizing anti-PD1 resistant tumors. Our findings suggest that combining Bv8 blockade with anti-PD1 therapy can be used as a strategy for overcoming therapy resistance.